2016
DOI: 10.1371/journal.pone.0162898
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Sarcopenic Obesity and Depressive Symptoms in Older Japanese Adults

Abstract: The effects of sarcopenic obesity, the co-existence of sarcopenia and obesity, on mood disorders have not been studies extensively. Our objective was to examine the association of depressive symptoms with sarcopenia and obesity status in older Japanese adults. We analyzed data from 1731 functionally-independent, community-dwelling Japanese adults aged 65 years or older (875 men, 856 women) randomly selected from the resident register of Kashiwa city, Chiba, Japan in 2012. Sarcopenia was defined based on append… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
3
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 40 publications
(49 reference statements)
5
61
3
4
Order By: Relevance
“…Conversely, in this study, body mass index was notably higher in men in the sarcopenia group; that is, sarcopenic obesity was a possibility. A previous study of older patients in the area reported a relationship between sarcopenia and depression . However, in the present study, where body mass index was adjusted using multivariate analysis in men, there was still a strong relationship between sarcopenia and depression.…”
Section: Discussioncontrasting
confidence: 83%
“…Conversely, in this study, body mass index was notably higher in men in the sarcopenia group; that is, sarcopenic obesity was a possibility. A previous study of older patients in the area reported a relationship between sarcopenia and depression . However, in the present study, where body mass index was adjusted using multivariate analysis in men, there was still a strong relationship between sarcopenia and depression.…”
Section: Discussioncontrasting
confidence: 83%
“…9,22,23 In these studies, however, only depressive symptoms were measured while no formal DSM-IV diagnosis was confirmed. 9,22,23 In these studies, however, only depressive symptoms were measured while no formal DSM-IV diagnosis was confirmed.…”
Section: Sarcopenic Obesity As a Potential Risk Factor For Depressionmentioning
confidence: 97%
“…14 Proposed mechanisms underlying this vicious circle between muscle loss and obesity are insulin resistance, inflammation, oxidative stress, and hormonal changes. 9,22,23 In the Korea National Health and Nutrition Examination Survey among community-based persons aged 20 years and older, sarcopenic obesity was associated with a lower level of psychological health and quality of life 9 but not with depression. 8,15 Sarcopenic obesity has been associated with metabolic and functional impairments as well as increased mortality rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, an accumulation of evidence has suggested that diagnoses of sarcopenia and sarcopenia with obesity are associated with depression (1922). However, large dataset studies have also reported findings on no associations between sarcopenia and depression (23, 24). …”
Section: Introductionmentioning
confidence: 99%